PENGARUH PROMOSI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA PT ALVA NIAGA BANINDO - Hendi, Hendi; Purba, Tiurniari (SCIENTIA JOURNAL, 2021)
The purpose of this study was to determine promotion and brand image that affect the purchase decision at PT Alva Niaga Banindo with the sampling technique used is non-probability sampling using saturation sampling for the number of samples 115. The results of the coefficient of determination (R2) obtained are the promotion variables and the brand image that is approved 66.7% of the purchasing decisions at PT Alva Niaga Banindo. From the results of multiple linear regression shows that Y = 8,951 + 0.783 (X1) + -0.131 (X2). T test results indicate promotion has an influence on purchasing decisions Sig = 0,000 <0.05; t-count = 14.936), and brand image is not required to significantly influence the purchasing decisions (Sig = 0.071> 0.05; t-calculate = -1,821). The f test results show that promotion and simultaneous brand image have a positive and significant influence on purchasing decisions at PT Alva Niaga Banindo (Sig = 0,000 <0.05; f-count = 112,408